2012
DOI: 10.1507/endocrj.ej11-0387
|View full text |Cite
|
Sign up to set email alerts
|

Association of IRS-1 and IRS-2 genes polymorphisms with polycystic ovary syndrome: a meta-analysis

Abstract: POLYCYSTIC OvarY SYndrOme (PCOS)is one of the most common heterogeneous endocrine disorders, which affect 5%-10% of women in reproductive age and is a leading causes of female infertility [1]. It is characterized by menstrual irregularity, hyperandrogenism, insulin resistance, and increased risk of type 2 diabetes mellitus (T2DM) and cardiovascular disease (CVD) [2,3]. Candidate genes for etiology of PCOS involve in ovarian and adrenal steroidogenesis, steroid hormone actions, gonadotropin action and regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 39 publications
0
28
1
Order By: Relevance
“…One case-control study replicated the insulin receptor (414), and several independent studies have reported evidence for an association with IRS-1 (417). Studies have not significantly associated the diabetes susceptibility region of the TCF7L2 gene with the PCOS reproductive phenotype, although studies have associated a novel region of the gene with PCOS-affected status (418).…”
Section: Candidate Gene Studiesmentioning
confidence: 99%
“…One case-control study replicated the insulin receptor (414), and several independent studies have reported evidence for an association with IRS-1 (417). Studies have not significantly associated the diabetes susceptibility region of the TCF7L2 gene with the PCOS reproductive phenotype, although studies have associated a novel region of the gene with PCOS-affected status (418).…”
Section: Candidate Gene Studiesmentioning
confidence: 99%
“…Recent four researches in the association between IRS-1 Gly972Arg polymorphism and PCOS still had different conclusions [38][39][40][41]. Very recent meta-analysis by Ruan Y in 2012 concluded that IRS-1 Gly972Arg polymorphism is associated with PCOS, and this variation might be considered as a risk factor for PCOS further this study also concluded that no significant association was detected between IRS-2 Gly1057Asp polymorphism and PCOS [12].…”
Section: Irs1 -Gly972arg Polymorphismmentioning
confidence: 79%
“…In the reproductive system, it stimulates ovaries to produce and secrete androgens, enhances ovarian growth, and inhibits apoptosis in the ovarian follicles, which may cause cyst formation [9,11]. Because insulin resistance, hyperinsulinaemia, and β-cell dysfunction are common features of PCOS, insulin, and the other members of insulinsignaling pathway have been considered to be candidates for PCOS [12]. A Variable Number of Tandem Repeats (VNTR) polymorphism located in the 5' regulatory element of the insulin gene INS, affects its transcriptional regulation, and is associated with hyperinsulinemia, fasting insulin levels, susceptibility to T2DM, birth weight, and childhood obesity and juvenile obesity [10].…”
Section: Insulin (Ins) Gene Polymorphism In Pcosmentioning
confidence: 99%
See 1 more Smart Citation
“…A Mendelian meta-analysis has confirmed significant association of IRS-1 (Gly972Arg) polymorphism with the risk of developing PCOS and impaired insulin signaling [36]. A recent meta-analysis also revealed significant association of IRS-1 Gly972Arg polymorphism with PCOS but not with IRS-2 Gly1057Asp polymorphism [55].…”
Section: Irsmentioning
confidence: 95%